Gestión informativa de los medios digitales en época de pandemia y su impacto en la calidad de la información que reciben los habitantes del Recinto Guantupi Bajo del cantón Valencia año 2022 - Mendoza Mendoza, Dayana Jamileth (2022)
This research work was embroidered with the topic of Informative Management and digital media in which it is of great importance for digital media since informing the population they spread knowledge to the inhabitants of the Guantupi Campus to strengthen knowledge and good information. spread by digital media during the pandemic in which to improve the use of communication and information. The main theories on information management were also identified with a media process by developing correct sources of information and establishing the conformity of the inhabitants, but also information consists of content of great importance for the ease of knowledge skills and dexterity in the inhabitants the quality of information among the inhabitants means communicating and connecting and sharing information.